Hooking Together Sigmoidal Monomers into Supramolecular Polymers1. (26th September 2019) - Carini, Marco; Marongiu, Mauro; Strutyński, Karol; Saeki, Akinori; Melle‐Franco, Manuel; Mateo‐Alonso, Aurelio
Abstract: Supramolecular polymers show great potential in the development of new materials because of their inherent recyclability and their self‐healing and stimuli‐responsive properties. Supramolecular conductive polymers are generally obtained by the assembly of individual aromatic molecules into columnar arrays that provide an optimal channel for electronic transport. A new approach is reported to prepare supramolecular polymers by hooking together sigmoidal monomers into 1D arrays of π‐stacked anthracene and acridine units, which gives rise to micrometer‐sized fibrils that show pseudoconductivities in line with other conducting materials. This approach paves the way for the design of new supramolecular polymers constituted by acene derivatives with enhanced excitonic and electronic transporting properties. Abstract : Die Sache hat einen Haken : Ein Ansatz zur Herstellung supramolekularer Polymere durch das Verhaken S‐förmiger Monomere in 1D‐Anordnungen π‐gestapelter Anthracen‐ und Acridin‐Einheiten wird vorgestellt. Die daraus resultierenden Mikrometer‐großen Fasern zeigen Pseudoleitfähigkeiten im Einklang mit anderen leitenden Materialien.